STOP-Bang as a predictor of obstructive sleep apnea-hypopnea syndrome in outpatients - John Carlos Pedrozo-Pupo; Jorge Armando Egurrola-Pedraza; Adalberto Campo-Arias (Duazary, 2021)
The STOP-Bang has been promoted as a valuable tool for identifying obstructive sleep apnea-hypopnea syndrome (OSAHS) in medical and surgical patients. However, its performance in Colombian samples is unknown. The objective of this study was to determine the clinimetric performance of the STOP-Bang index versus the study of polysomnography in patients from Santa Marta, Colombia. An accuracy study of diagnostic tests with a test-based approach was designed. Seven hundred sixty-two adults referred for polysomnography to evaluate OSAHS were included in the research. They were aged between 18 and 94 years old (mean=47.2, SD=13.4), 63.3% were men, and 46.5% were classified as obese. The STOP-Bang performance was compared against the best reference criterion, the hypopnea/apnea index determined by polysomnography. The diagnosis of OSAHS was confirmed in 461 (60.5%) and corroborated in 301 (39.5%). The area under the curve was 0.70 (95%CI 0.66-0.74), and the best cut-off point was 4, with a sensitivity of 79.2%, a specificity of 53.5%, the positive predictive value of 72.2%, the negative predictive value of 62.6%, positive likelihood ratio was 1.70, negative likelihood ratio was 0.39; OR=4.08 (CI95% 2.99-5.56) and Cohen's kappa of 0.33. As conclusions, performance indicators show that STOP-Bang...